MEMBACA EKSISTENSI ‘PUSAT LITERASI’ DARI PELOSOK NEGERI: IRONI PENGELOLAAN PERPUSTAKAAN MADRASAH ALIYAH KONAWE SELATAN: READING THE EXISTENCE OF A REMOTE LITERACY CENTER: AN IRONY OF LIBRARY MANAGEMENT IN MADRASAH ALIYAH (ISLAMIC SENIOR HIGH SCHOOLS) SOUTH KONAWE - Abu Muslim (Penamas, 2015)
This study invites us to see the real condition of libraries in South Konawe. Using the qualitative descriptive research methods, this study aims to know library management in Islamic Senior High School education level. The research targets were purposively selected for three private or public Islamic Senior High Schools, which represent levels of accreditation. They are MAN Konda (accreditation B), MA Al-Amin Mataiwoi (accreditation C), MA DDI Nurul Qalby Ranomeeto (has not accredited yet). The results showed that the conditions of library management in three Madrasah Aliyah are very limited and not professional. They are limitted in terms of infrastructure and books collection. Also, they are not professional regarding to the implementation of library services, since there no guidelines or specific system running the libraries. The role of stakeholders in the library development needs to be improved on intensification of technical assistance and coordination aspects based on madrasa needs. This study also found that in Madrasah Aliyah level, library development is not a priority, since other madrasah infrastructure remains inadequate. Keywords: Management, Library, South Konawe, MA, Irony Penelitian ini mengajak kita melihat kondisi riil perpustakaan di Konawe Selatan dengan mengoperasionalkan metode penelitian kualitatif deskriptif untuk memperoleh gambaran pengelolaan perpustakaan di tingkat satuan pendidikan Madrasah Aliyah. Sasaran penelitian dipilih secara purposive 3 Madrasah Aliyah negeri/swasta, yang masing-masing mewakili tingkatan akreditasi, yakni: MAN Konda (akreditasi B), MA Al- Amin Mataiwoi (akreditasi C), dan MA DDI Nurul Qalby Ranomeeto (tidak/belum terakreditasi). Hasil penelitian menunjukkan, bahwa kondisi pengelolaan perpustakaan Madrasah Aliyah di ketiga madrasah sasaran dikelola dengan serba terbatas dan serba otodidak. Terbatas dari segi sarana prasarana dan koleksi buku serta otodidak dari segi pelaksanaan pelayanan yang semuanya dilakukan tanpa pedoman dan/atau sistem khusus yang dipegangi. Peran stakeholder dalam pengembangan perpustakaan dinilai masih perlu peningkatan dari aspek intensifikasi bantuan teknis serta aspek koordinasi berbasis kebutuhan madrasah. Penelitian ini juga menemukan, bahwa sesungguhnya di tingkat satuan pendidikan Madrasah Aliyah, pengembangan perpustakaan bukan menjadi prioritas utama, sebab sarana prasarana madrasah lainnya pada kenyataannya juga masih belum memadai. Kata Kunci: Pengelolaan, Perpustakaan, Konawe Selatan, MA, ironi